Prevalence of oral lesions in 25 years of Oral Cancer Prevention campaigns in Paraná State, Brazil, 1988 to 2013 - Laurindo Moacir Sassi; Gyl Henrique A. Ramos; Jose Luís Dissenha; Juliana Lucena Schussel; Maria Isabela Guebur; Cleverson Patussi (Revista Sul-Brasileira de Odontologia, 2015)
Epidemiological studies add up as a large area of scientific research and play an important role revealing the prevalence of the several diseases in the place where they applied. Public and health professionals have become more aware of the importance of oral mucosal lesions. Objective: To determine the frequency of the oral lesions and determinate the epidemiological profile of patients attending the prevention of oral cancer campaigns in the state of Paraná, Brazil, between 1988 and 2013. Material and methods: A prospective study was conducted evaluating 25 years of oral cancer prevention campaigns in the state of Paraná, Brazil, between 1988 and 2013. All patients were evaluated in a systematic way and were older than 30 years, answering one questionnaire with data relating to harmful health habits, family history of cancer, family income, frequency of visits to dentists and knowledge on the subject. Results: A total of 22,300 patients were evaluated during the 25 years of projects and 3,731 had oral lesions, while 18,569 patients had no oral alterations during the evaluation. Among those patients, 13779 (61.78%) were female and 8521 (38.78%) were male, 843 (22.59%) were smokers, 578 (15.49%) used alcohol and in 1386 (37.14%) had the habit of using yerba mate. The prevalence of lesions occurred as follows: 533 (14.28%) cases of lesions with aspect of leukoplakia, 1095 (29.34%) inflammatory lesions, 1934 (51.83%) of traumatic origin and 169 (4 5%) classified as other. Conclusion: The campaigns have brought benefits to the health of the elderly population but it is still not enough to make up for low levels of oral lesions appearance. Education of the population should in this way be approached more seriously and effectively.